Effects of brief intervention on subgroups of injured patients who drink at risk levels. Issue 3 (29th June 2015) - Cochran, Gerald; Field, Craig; Foreman, Michael; Ylioja, Thomas; Brown, Carlos V R
Abstract : Alcohol-related injuries are a major source of admission for trauma care. Screening and brief intervention (SBI) for injured patients can result in decreased drinking and risk behaviors. It is not clear SBI is equally beneficial for all injured patients. A secondary data analysis of 553 patients admitted to two Level-1 trauma centers was conducted. Latent class analysis was used to identify patient subgroups based on injury-related risks and consequences of alcohol use. Intervention effects on drinking were examined among subgroups. Five subgroups were identified. Drinking improved in patients reporting multiple risks and injuries/accidents and drinking and driving. Patients that reported drinking and driving and taking foolish risks or fighting while drinking and taking foolish risks did not show improvements. Trauma centers may benefit from targeting interventions based on injury-related risks and consequences of alcohol use. Further research is needed to test bedside approaches for tailored interventions.